2017
DOI: 10.1111/1750-3841.13947
|View full text |Cite
|
Sign up to set email alerts
|

Shelf‐Life of Boiled Salted Duck Meat Stored Under Normal and Modified Atmosphere

Abstract: The objective of this study was to investigate the physicochemical properties and changes in the microbial counts of boiled salted duck (BSD) meat packed under various conditions. BSD meat was stored under normal atmosphere (C) and two modified atmosphere packaging (MAP) conditions: M1 (N 2 , 100%) and M2 (CO 2 /N 2 , 30%/70%) at 4°C. Microbiological quality, pH, redness, lipid oxidation, headspace gas composition, and water activity of BSD meat were measured. The results showed that the time to reach the maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…This finding is in agreement with the results reported by Zhai et al. () and Dogu‐Baykut and Gunes ().…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…This finding is in agreement with the results reported by Zhai et al. () and Dogu‐Baykut and Gunes ().…”
Section: Resultssupporting
confidence: 94%
“…Modified atmosphere packaging (MAP) has gradually been used in the storage of cooked meat products in recent years, and has proven to be an effective storage method that can significantly extend the shelf life of products (Karpińska‐Tymoszczyk, ; Patsias, Chouliara, Badeka, Savvaidis, & Kontominas, ; Zhai et al., ). MAP can also adjust the gas composition of the sample to achieve the desired storage effect (Cooksey, ; Mcmillin, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with the findings of the study by Brannan (2010) , in which GSE had no effects on the moisture content or pH of the chicken pie during storage. This result is also similar to the report by Zhai et al. (2017) , who studied the pH changes during the storage of MAP salted ducks.…”
Section: Resultssupporting
confidence: 92%
“…Gao et al (2013) found that the increase in pH value was due to alkaline substances produced by enzymatic hydrolysis of meat proteins by microorganisms. However, Zhai et al (2018) found that LAB metabolism produces lactic acid, which leads to a decrease in meat pH value. Hence, the correlation analysis between microbial flora and physicochemical properties is very crucial to improve quality of the meat products.…”
Section: Introductionmentioning
confidence: 99%